Four new species of Actinopus (Mygalomorphae: Actinopodidae) from Uruguay - Duniesky, Rios-Tamayo (Zootaxa, 2019)
Actinopus specimens from different localities in Uruguay that did not match any of the previously species present in the country were examined, and four new species are described: A. coboi sp. nov., from Colonia province; A. fernandezi sp. nov., from Salto province; A. simoi sp. nov., from Maldonado province; and A. uruguayense sp. nov., from Colonia and Cerro Largo provinces. The record of the species A. longipalpis for Montevideo is rejected and A. liodon is considered “species inquirenda”. Actinopus coboi has spermathecae with an apical lobe diagonally directed; A. fernandezi is characterized by a stylized copulatory bulb and its greater number of retrolateral thorns on tibia II. Actinopus simoi can be distinguished from A. uruguayense by its carapace with a dark coloration; a reddish coloration in the palpal tibia and the shape of its spermathecae and copulatory bulb. With the presence of the Argentinian species—A. gerschiapelliarum, A. puelche and A. insignis—the number of species known in the country is increased to nine. All new species are diagnosed and illustrated; a dichotomous key to all species of Actinopus from Uruguay is also provided.